Scientific Traditions in the Ancient Mediterranean and Near East: Joint Proceedings of the 1st and 2nd Scientific Papyri from Ancient Egypt International Conferences, May 2018, Copenhagen, and September 2019, New York - Schiødt, Sofie; Jacob, Amber; Ryholt, Kim (New York University Press, 2023)
Comparative insights on astronomy, divination, and medicine from ancient textsThe contributions in this volume revolve around a set of interconnected topics in the ancient sciences: medicine, astronomy, astrology, and divination. Several essays present unpublished textual sources or editions of new source material on divination (e.g., dream interpretation, personal astrology, and Sothis divination) and medicine (e.g., dermatology, gynecology, and apotropaic incantations). Other contributions provide new insights into known corpora or texts, such as the Assyro-Babylonian omens, the Hippocratic treatise Places in Man, Greco-Egyptian medical texts, and the vast astronomical corpus of Greco-Roman Egypt. The interdisciplinary milieu in which these essays were generated, under the aegis of the international Scientific Papyri from Ancient Egypt (SciPap) project, means that many of the studies embrace an explicitly and well-researched cross-cultural and comparative approach, revealing similarities in both certain conceptualizations of disease and healing, and astronomical literature and divinatory practice, across the Mediterranean and Near East. This book will be of interest primarily to specialists in the history of medicine, science, divination, and magic, as well as to papyrologists, Egyptologists, and Assyriologists
Keywords: Konferenzschrift -- 2018 -- Kopenhagen; Wissenschaftstransfer; Kulturaustausch; Magie; Astrologie; Astronomie; Medizin; Mittelmeerraum; Alter Orient; Ägypten